Black-Gray-White Barcode Based on Error Correction Data Encoding - Dychka, Ivan; Sulema, Olga (Journal of Applied Computer Science, 2019)
The paper presents an approach based on using barcodes with three color gradations (white, gray, and black) instead of traditional black and white barcodes. Such three-color barcodes can be produced and read by using the same equipment as usual black and white barcodes, but due to the third color they have a higher information density. It is shown in the paper that in order to ensure high reliability and accuracy of barcoded information reading, it is necessary to encode the data with a Reed-Solomon correction code which is capable of correcting multiple errors. The method of data encoding and decoding in the Galois field GF(3m), where m is the degree of an irreducible polynomial, is proposed. The noise immunity of the black-gray-white barcode capable of multiple errors correction based on Reed-Solomon code is analyzed and discussed as well.